Impact of the COVID-19 pandemic on lung cancer screening utilization and outcome: a health examination center retrospective study - Chi-Shen Chen; Cai-Sin Yao; Fu-Zong Wu (Annals of Medicine)
Background The coronavirus disease 2019 (COVID-19) pandemic has disrupted healthcare systems, significantly affecting preventive services such as low-dose computed tomography (LDCT) for lung cancer screening. We aimed to evaluate the pandemic’s impact on LDCT screening practices at Kaohsiung Veterans General Hospital, focusing on the changes in participation rates, Lung-RADS categories, and lung cancer diagnoses to guide the development of interventions for improving screening programs and early detection during health crises.Materials and methods A retrospective cohort of 56,730 individuals who underwent health examinations between 2017 and 2023 was analyzed. Data on demographics, smoking history, family history of lung cancer, and eligibility for LDCT subsidies in Taiwan were obtained. Screening utilization and outcomes were cross-referenced with cancer registries and imaging databases. A subset of 17,743 individuals who underwent LDCT were examined to determine the pre- and post-COVID19 differences in smoking prevalence, family history, high-risk Lung Imaging Reporting and Data System (Lung-RADS) categories (3 or 4), and lung cancer diagnoses.Results Following the implementation of the level 3 alert, notable shifts were observed in smoking habits and lung cancer screening eligibility. The prevalence of heavy smokers (≥30 pack-years) declined from 6.9% before the alert to 6.1% after (p = 0.002). Conversely, the proportion of individuals with a family history of lung cancer qualifying for LDCT screening increased significantly from 6.0% to 6.6% (p = 0.009). Additionally, the prevalence of lung cancer diagnoses among individuals with high-risk Lung-RADS categories (Lung-RADS 3 or 4) decreased significantly from 21.5% before the alert to 13.4% after (p = 0.037).Conclusion The pandemic disrupted LDCT screening, reducing access for high-risk smokers while increasing non-smoker participation. High-risk nodules declined but partially recovered post-pandemic. Future policies must prioritize high-risk individuals, optimize resources, and enhance early detection to improve outcomes and crisis preparedness.